Assessment of differences on inflammatory and metabolic indicators between pre- and post-menopause women among hypertensive and/or diabetic patients - Ellulu, Mohammed S.; Rahmat, Asmah; Abed, Yehia; Baloushah, Suha; Ismail, Patimah; Khaza'ai, Huzwah (Academic Journals, 2015)
To assess the differences on inflammatory and metabolic indicators between pre-menopause and post-menopause women among hypertensive and/or diabetic type-2 women. A total of 236 obese women included in the study have chosen from Primary Health Care Centers in Gaza City, Palestine, through a cross-sectional study. Selection depended on health status hypertensive and/or diabetic type-2 (HT, T2DM, HT+T2DM). In HT group, post-menopause women had significant higher values than pre-menopause women on TC (200±47 vs. 172.5±55 mg dL–1, p<0.01) and TG (166±89 vs. 120.5±82 mg dL–1, p<0.01). In T2DM group, post-menopause women had significant higher values than pre-menopause women on SBP (132±24 vs. 120±20 mm Hg, p<0.01), TC (213±40 vs. 185±46 mg dL–1, p<0.05) and TG (196±118 vs. 136±64 mg dL–1, p<0.05). Finally, in HT+T2DM group, post-menopause women had significant higher value than pre-menopause women on SBP (144±21 vs. 133±14 mmHg, p<0.05), TC (214±54 vs. 181±55 mg dL–1, p<0.05), TG (231±83 vs. 158±85 mg dL–1, p<0.05), IL-6 (2.32±1.34 vs. 1.71±1.45 pg mL–1, p<0.05) and BMI (36.48±7.1 vs. 32.18±5.6 kg m‾ 2, p<0.05). Post-menopause women diseased of HT and T2DM accompanied with higher rates of BMI are at risk for developing inflammatory and metabolic morbidities.